120 years of Trapist cheese - Slavko Kirin (Mljekarstvo)
Last year Trapist cheese, the product of the monastery Marija Zvijezda in Banja Luka, celebrated 120 years of its production. The aim of this paper is to present, through historical development and Trapist cheese characteristics, such an important anniversary to Croatian cheese making industries. The paper describes the way of Trapist cheese from France to Banja Luka, from where it was spread through many countries, especially to former Austro- Hungarian empire. On its way it was also adopted by Croatia through the lastcentury. Organoleptic properties of Trapist cheese, from different origin, as well as its comparison with Saint-Paulin cheese, which can be considered as heritable of the original Port-du Salut, i.e. Port-Salut, are also presented. The same comparison is made with regard to technological process and chemical composition. As a conclusion it is recommended that Croatian types of Trapist cheese should be protected by legislation and defined as standard types.